Parental separation and parental mental health in childhood and tinnitus and hyperacusis disability in adulthood: a retrospective exploratory analysis. - Aazh, Hashir; Langguth, Berthold; Danesh, Ali A. (International Journal of Audiology, 2018)
Objectives: To explore the relationships between parental separation and parental mental health in childhood with tinnitus and hyperacusis disability in adulthood. Design: Retrospective cross-sectional. Study sample: The data for consecutive patients who attended a tinnitus and hyperacusis clinic in the UK over a six months period were included (n = 184). Results: 14.7% of patients reported that while they were growing up, their parents were separated or divorced. There were no significant differences in Tinnitus Handicap Inventory (THI) and Hyperacusis Questionnaire (HQ) between patients with and without history of parental separation. About 40.2% reported history of mental health disorders in their parents. The scores on THI and HQ were worse in the group that reported mental health disorders in their parents (p < .01). Parental mental health illness did not significantly relate to THI, however, it was significantly related to the risk of hyperacusis (odds ratio [OR], after adjusting for age and gender: 2.05, p = .026). The adjusted OR for a subgroup of patients with a diagnosis of hyperacusis was 6.7 (p = .011), indicating a stronger relationship for this subgroup. Conclusions: Among patients seeking help for their tinnitus and hyperacusis, poor parental mental health was associated with increased hyperacusis disability.